Orbital Wall Restoring Surgery for Inferomedial Blowout Fracture. Issue 8 (November 2015) - Lim, Nam Kyu; Kang, Dong Hee; Oh, Sang Ah; Gu, Ja Hea
Abstract : Abstract: Repairing a large inferomedial blowout fracture remains a challenge to orbital surgeon. The authors restored the fracture using combined transnasal and transorbital approaches using support of both paranasal sinuses. The authors compared surgical results of this novel method with those of the traditional procedure. Of 106 inferomedial blowout fracture patients who underwent surgical treatment between March 2007 and July 2013, 50 patients were selected in our study: 25 patients underwent the traditional procedure as controls, and the other 25 patients underwent orbital wall restoring surgery by our combined approach. Outcomes were evaluated in terms of the orbital volume ratio (OVR) and changes in Hertel scale. The OVR in the experimental group (7.19%) decreased more significantly than in the control group (2.71%) ( P  < 0.05). In conclusion, the orbit was restored more successfully following orbital wall restoring surgery with dual support than by using the traditional inferomedial blowout fracture procedure.